PENGARUH ONLINE SHOP DAN GAYA HIDUP HEDONISME TERHADAP PERILAKU KONSUMTIF MAHASISWI FEBI UIN STS JAMBI MENURUT PERSPEKTIF ISLAM (Studi pada Mahasiswi Aktif Fakultas Ekonomi dan Bisnis Islam) - Winy Meldiani; Nurlia Fusfita; Erwin Saputra Siregar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The aim of this research is to determine the influence of online shops and hedonistic lifestyles on the consumer behavior of FEBI UIN STS Jambi students from an Islamic perspective. Meanwhile, this type of research uses a quantitative approach method with the types of data used are primary data and secondary data obtained from questionnaires. The population in this study were students from the Faculty of Economics and Islamic Business, UIN STS Jambi. The sampling method uses non-probability sampling and random sampling. The research results show that the Onlineshop Variable (X1) partially has a positive effect on Student Consumptive Behavior. The results of the research show that the Online Shop has a significance value of 0.000<0.05, which means the hypothesis shows that the Online Shop has a positive and significant effect on Student Consumptive Behavior. Hedonistic Lifestyle (X2) partially has a positive effect on Student Consumptive Behavior. The results of the research show that the Hedonistic Lifestyle has a significance value of 0.027 <0.05, which means the hypothesis shows that the Hedonistic Lifestyle has a positive and significant effect on Student Consumptive Behavior, and there is a simultaneous positive and significant influence between the influence of the Onlineshop and the Hedonistic Lifestyle on Student Consumptive Behavior. This is based on the results of ANOVA calculations where the significance value is 0.000 < 0.05.